Positioning of quality systems in lean manufacturing: integrated approach vs independent implementation in the food industry - Sitorus, Helena; Budianto, Budianto; Feri, Zefki Okta; Nurlaila, Qomarotun; Suryatman, Tina Hernawati; Fitra, Fitra (SINERGI, 2025)
Despite the widespread adoption of Lean Manufacturing (LM), its effectiveness in the food industry remains underexplored, particularly regarding the integration of the Quality System (QS). The purpose of this research is to compare QS placement and LM implementation strategies in the food industry. This study utilized a comparative approach, analyzing empirical data from four food processing companies in Indonesia over six months, employing qualitative methods (expert interviews, document analysis) and quantitative analysis. Response Surface Methodology (RSM) with the Box-Behnken design was applied for optimization, while Principal Component Analysis (PCA) identified key variables influencing Lean Manufacturing success. Two implementation strategies were compared: phased implementation with a separate Quality System (Companies A and B) and simultaneous implementation with an integrated Quality System (Companies C and D). The findings revealed that Company A achieved the highest performance, with 88% in 5S and 85% in Just-In-Time (JIT), followed by Company B with 80% in JIT and 75% in 5S. In contrast, companies C and D exhibited lower performance. PCA results indicated that PC1 (80.40%) was associated with on-time delivery and sales growth, whereas PC2 (14.47%) was linked to rejection factors. Companies A and B excelled in PC1, while Companies C and D were more dominant in PC2. These findings suggest that phased implementation of LM tools is more effective than simultaneous application. This research not only addresses a critical gap in the literature but also provides practical insights for food industry practitioners seeking to enhance operational efficiency through Lean Manufacturing.